2022
DOI: 10.1093/cid/ciac115
|View full text |Cite
|
Sign up to set email alerts
|

Genital Immune Cell Activation and Tenofovir Gel Efficacy: A Case-Control Study

Abstract: Genital inflammation (GI) undermines topical HIV pre-exposure prophylaxis (PrEP) efficacy through unknown mechanisms. Here, associations between activated endocervical CD4+ T cell numbers and higher deoxyadenosine triphosphate (dATP) concentrations suggest that competition for intracellular metabolites within HIV target cells may reduce the efficacy of antiretroviral-based PrEP in women with GI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“…This was similarly the finding with CD1a + cells in the foreskin showing that epithelial dendritic cells [ 21 , 30 ] and/or epidermal Langerhans cells [ 23 ] were consistently present across the different trial arms but unchanged in numbers. In contrast to studies using topical PrEP whereby 1% tenofovir gel increased T-cell densities in rectal tissue [ 11 ] and CD4 + T-cell activation in endocervical tissue [ 13 ], we show in our study that oral PrEP dosing has no effect on local foreskin T-cell immunity. Previously, we showed that the CHAPS study resulted in modulation of gene expression in the foreskin resulting in a potentially unfavourable environment for HIV replication [ 18 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This was similarly the finding with CD1a + cells in the foreskin showing that epithelial dendritic cells [ 21 , 30 ] and/or epidermal Langerhans cells [ 23 ] were consistently present across the different trial arms but unchanged in numbers. In contrast to studies using topical PrEP whereby 1% tenofovir gel increased T-cell densities in rectal tissue [ 11 ] and CD4 + T-cell activation in endocervical tissue [ 13 ], we show in our study that oral PrEP dosing has no effect on local foreskin T-cell immunity. Previously, we showed that the CHAPS study resulted in modulation of gene expression in the foreskin resulting in a potentially unfavourable environment for HIV replication [ 18 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Tenofovir gel has been evaluated for vaginal and rectal PrEP [ 11 , 12 ], with the CAPRISA 004 study [ 12 ] showing up to 54% lower HIV incidence in women in the gel arm. However, women receiving 1% tenofovir gel had an accumulation of activated endocervical CD4 + T cells, which were associated with increased drug metabolite levels in the tissue [ 13 ]. Although these studies focused on topically applied PrEP, their findings raise the issue of host immune activation in response to drug, which may undermine the potential efficacy of PrEP.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that when TFV concentrations are below ideal levels, factors that increase target cell presence on the mucosal surface, such as inflammation or damage, would overcome the TFV protective effects. This concept is supported by CAPRISA 004 clinical data describing ideal conditions for increased intracellular metabolite competition and reduced drug efficacy in the context of inflammation and immune cell activation ( 93 ).…”
Section: Challenges To Effective Prevention Strategies In Womenmentioning
confidence: 92%